Development of a novel gene signature in patients without Helicobacter pylori infection gastric cancer. Issue 2 (21st October 2019) - Lv, Xuemei; Zhao, Yanyun; Zhang, Liwen; Zhou, Shuqi; Zhang, Bing; Zhang, Qiang; Jiang, Longyang; Li, Xueping; Wu, Huizhe; Zhao, Lin; Wei, Minjie; He, Miao
Abstract: Gastric cancer (GC) is one of the most fatal common cancers in worldwide. Helicobacter pylori ( H. pylori ) infection is closely related to the development of GC, although the mechanism is still unclear. In our study, we aim to develop a robust messenger RNA (mRNA) signature associated with H. pylori (‐) GC that can sensitively and efficiently predict the prognostic. The RNA‐seq expression profile and corresponding clinical data of 598 gastric cancer samples and 63 normal samples obtained from The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus database. Using gene set enrichment analysis H. pylori (+) GC and H. pylori (‐) GC patients and normal samples to select certain genes for further analysis. Using univariate and multivariate Cox regression model to establish a gene signature for predicting the overall survival (OS). Finally, we identified G2/M related seven‐mRNA signature ( TGFB1, EGF, MKI67, ILF3, INCENP, TNPO2, and CHAF1A ) closely related to the prognosis of patients with H. pylori (‐) GC. The seven‐mRNA signature was identified to act as an independent prognostic biomarker by stratified analysis and multivariate Cox regression analysis. It was also validated on two test groups from TCGA and GSE15460 and shown that patients with high‐risk scores based on the expression of the seven mRNAs had significantly shorter survival times compared to patients with low‐risk scores ( P < .0001). In this study, we developed a seven‐mRNA signature related to G2/M checkpoint from H. pylori (‐) GCs that as an independent biomarker potentially with a good performance in predicting OS and might be valuable for the clinical management for patients with GC. Abstract : In the present study, we developed a seven‐messenger RNA signature related to G2/M checkpoint from Helicobacter pylori (‐) gastric cancers (GCs) that as an independent biomarker potentially with a good performance in predicting overall survivals and might be valuable for the clinical management for patients with GC.